Ultra-high electrostriction and ferroelectricity in poly (vinylidene fluoride) by ‘printing of charge’ throughout the film - Zhang, Ningyi; Dong, Xiaobing; He, Shihui; Liang, Zhao; Li, Weipeng; Qian, Qihao; Jiang, Chao (Nature communications, 2025)
Electrostriction is an important electro-mechanical property in poly (vinylidene fluoride) (PVDF) films, which describes the proportional relation between the electro-stimulated deformation and the square of the electric field. Generally, traditional methods to improve the electrostriction of PVDF either sacrifice other crystalline-related key properties or only influence minimal regions around the surface. Here, we design a unique electret structure to fully exploit the benefits of internal crystal in PVDF films. Through the 3D printing of charged ink, we have obtained the best electrostrictive and ferroelectric properties among PVDF-based materials so far. The optimized electrostrictive coefficient M 33 (324 × 10 −18 m 2 V −2 ) is 10 4 times that of normal PVDF films, and the piezoelectric constant d 33 (298 pm V −1 ) is close to 10 times its traditional limit. The proposed 3D electret structure and the bottom-up approach to ‘print the charge’ open up a new way to design and adapt the electroactive polymers in smart devices and systems. The authors make a high-density charge structure to enhance the electrostriction of pristine poly (vinylidene fluoride), improving its ferroelectric performance to nearly 10 times its traditional limit.